The CHEOPS view of the climate of WASP-3 b - Scandariato, G.; Carone, L.; Cubillos, P. E.; Maxted, P. F. L.; Zingales, T.; Günther, M. N.; Heitzmann, A.; Lendl, M.; Wilson, T. G.; Bonfanti, A.; Bruno, G.; Krenn, A.; et al. (Astronomy and astrophysics (Berlin), 2024)
Context . Hot Jupiters are giant planets subject to intense stellar radiation. The physical and chemical properties of their atmosphere make them the most amenable targets for atmospheric characterization. Aims . In this paper we analyze the photometry collected during the secondary eclipses of the hot Jupiter WASP-3 b by CHEOPS, TESS, and Spitzer . Our aim is to characterize the atmosphere of the planet by measuring the secondary eclipse depth in several passbands and constrain the planetary dayside spectrum. Methods . We updated the radius and the ephemeris of WASP-3 b by analyzing the transit photometry collected by CHEOPS and TESS. We also analyzed the CHEOPS, TESS, and Spitzer photometry of the occultations of the planet, measuring the eclipse depth at different wavelengths. Results . Our update of the stellar and planetary properties is consistent with previous works. The analysis of the occultations returns an eclipse depth of 92±21 ppm in the CHEOPS passband, 83±27 ppm for TESS, and >2000 ppm in the IRAC 1-2-4 Spitzer passbands. Using the eclipse depths in the Spitzer bands, we propose a set of likely emission spectra that constrain the emission contribution in the CHEOPS and TESS passbands to approximately a few dozen parts per million. This allowed us to measure a geometric albedo of 0.21±0.07 in the CHEOPS passband, while the TESS data lead to a 95% upper limit of ∼0.2. Conclusions . WASP-3 b belongs to the group of ultra-hot Jupiters that are characterized by a low Bond albedo (<0.3±0.1), as predicted by different atmospheric models. On the other hand, it seems to efficiently recirculate the absorbed stellar energy, which is not typical for similar, highly irradiated planets. To explain this inconsistency, we propose that other energy recirculation mechanisms are at play besides advection (for example, the dissociation and recombination of H 2 ). Another possibility is that the observations in different bandpasses probe different atmospheric layers; this would make the atmospheric analysis difficult without an appropriate modeling of the thermal emission spectrum of WASP-3 b, which is not feasible with the limited spectroscopic data available to date.